ANALGESIC USE AND ASSOCIATED ADVERSE EVENTS IN PATIENTS WITH CHRONIC KIDNEY DISEASE: A SYSTEMATIC REVIEW - Ma’bud, Tasia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Chronic kidney disease and pain substantially impact the quality of life and hospital costs worldwide. Treating these conditions can be challenging due to characteristic pharmacokinetic and pharmacodynamic challenges. Aim: This study aims to identify the correlation between analgesic consumption and adverse outcomes in individuals with chronic kidney disease. Methods: The study complied with PRISMA 2020 guidelines and applied a timeframe of 2013-2023 to ensure similarity through comparison with existing literature. Specialists used online reference databases such as Pubmed and SagePub to identify review articles, preexisting publications, and incomplete works. Result: 219 and 112 articles have been extracted from PubMed and SagePub, respectively. In 2013, we collected 12 papers accomplishing specific research criteria, consisting of 8 from PubMed and 4 from SagePub. Conclusion: Patients with CKD require a strategy to minimize adverse consequences and maximize beneficial effects.